2022
DOI: 10.1155/2022/7936236
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment and Test-case Study of Wi-Fi Security through the Wardriving Technique

Abstract: This study aims to investigate Wireless Local Area Network (WLAN) within the context of its applicability as a 21st-century business tool and its survivability in a security threat-infested cyber landscape. WLAN security leverages the Wardriving technique deployed within geolocation to scan for WLAN density and explore the associated security mechanisms. Specifically, the study adopts two approaches; the first part reviews relevant research articles in electronic libraries and databases on WLAN security based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…After conducting a series of tests on the security conditions of the existing Wi-Fi network at the Directorate of Innovation and Business Incubator, researchers have successfully identified various vulnerabilities and weak points in the network infrastructure. These results are the basis for ongoing anticipation to increase the level of Wi-Fi network security from attacks that could potentially threaten network users (Etta et al, 2022). The security improvements that will be implemented based on the results of the penetration testing that has been carried out can be seen in table 4.…”
Section: Resultsmentioning
confidence: 99%
“…After conducting a series of tests on the security conditions of the existing Wi-Fi network at the Directorate of Innovation and Business Incubator, researchers have successfully identified various vulnerabilities and weak points in the network infrastructure. These results are the basis for ongoing anticipation to increase the level of Wi-Fi network security from attacks that could potentially threaten network users (Etta et al, 2022). The security improvements that will be implemented based on the results of the penetration testing that has been carried out can be seen in table 4.…”
Section: Resultsmentioning
confidence: 99%
“…A 2022 study suggested that private WLANs are predominantly encrypted using WPA2 or less secure protocols, four years after the publication of WPA3 [ 37 ]. When probing 21,345 WLANs in Cyprus, they found that only 13 networks employed WPA3.…”
Section: Background and Related Workmentioning
confidence: 99%
“…If the SSID and network security key are leaked to a third party, they can connect to the wireless LAN. Currently, there is a practice among criminal hackers called "wardriving", in which searches for vulnerable access points around a city are conducted while driving in cars along city streets 5 .…”
Section: Introductionmentioning
confidence: 99%